2009
DOI: 10.1186/1471-2288-9-55
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the placebo response in antimuscarinic drug trials for overactive bladder

Abstract: BackgroundThe purpose of this analysis was to characterize the placebo response in antimuscarinic drug trials for OAB, based on changes in commonly-used efficacy endpoints.MethodsPlacebo arm data for incontinence episodes, micturitions, voided volume and study characteristics were extracted from randomized placebo controlled antimuscarinic drug trials in OAB, from studies identified in a prior meta-analysis, and from a systematic review of more recently published studies. Relationships between variables were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 40 publications
0
46
2
Order By: Relevance
“…The results of the present study also differ from the results of the pooled analysis of fixed‐dose fesoterodine studies10 in that there were fewer endpoints with statistically significant differences between subjects receiving fesoterodine and those receiving placebo in the present study, whereas fesoterodine 4 and 8 mg both produced significantly greater improvement in most endpoints versus placebo in the pooled analysis of fixed‐dose studies 10. While robust placebo effects are common in OAB trials,18, 19 due perhaps at least in part to the practice of recording voiding habits in a bladder diary, the atypically large effect among placebo non‐escalators in the present study may suggest that subjects exhibiting the strongest placebo effect were self‐selected into the non‐escalator group. This may explain the lack of difference between fesoterodine and placebo non‐escalators.…”
Section: Discussioncontrasting
confidence: 91%
“…The results of the present study also differ from the results of the pooled analysis of fixed‐dose fesoterodine studies10 in that there were fewer endpoints with statistically significant differences between subjects receiving fesoterodine and those receiving placebo in the present study, whereas fesoterodine 4 and 8 mg both produced significantly greater improvement in most endpoints versus placebo in the pooled analysis of fixed‐dose studies 10. While robust placebo effects are common in OAB trials,18, 19 due perhaps at least in part to the practice of recording voiding habits in a bladder diary, the atypically large effect among placebo non‐escalators in the present study may suggest that subjects exhibiting the strongest placebo effect were self‐selected into the non‐escalator group. This may explain the lack of difference between fesoterodine and placebo non‐escalators.…”
Section: Discussioncontrasting
confidence: 91%
“…A higher randomization ratio (90) was noted as a design factor driving higher PR in psoriasis, and lower symptom severity at baseline (86,93) as patient-based factor driving the PR.…”
Section: Resultsmentioning
confidence: 99%
“…Both US and European analyses have concluded that no drug is consistently more effective than another [5,7,22] and the focus here is pharmacological versus behavioral approaches, not on comparison of individual drugs. The drug treatments reviewed were extended-release tolterodine, extended-release oxybutynin, trospium, solifenacin, darifenacin, and fesoterodine; all have been studied extensively for the treatment of incontinence [13,14,[23][24][25][26][27]. Figure 1 shows the treatment pathway for FBT for illustration; the other two treatments follow the same model.…”
Section: Treatment Options and Modelsmentioning
confidence: 99%